2014
DOI: 10.1128/aac.00096-14
|View full text |Cite
|
Sign up to set email alerts
|

Target Enzyme Mutations Confer Differential Echinocandin Susceptibilities in Candida kefyr

Abstract: cCandida kefyr is an increasingly reported pathogen in patients with hematologic malignancies. We studied a series of bloodstream isolates that exhibited reduced echinocandin susceptibilities (RES). Clinical and surveillance isolates were tested for susceptibilities to all three echinocandins, and those isolates displaying RES to one or more echinocandins were selected for molecular and biochemical studies. The isolates were analyzed for genetic similarities, and a subset was analyzed for mutations in the echi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…However, a few major errors were found for anidulafungin in two C. tropicalis isolates with FKS1 mutations that were classified as anidulafungin-susceptible and micafunginresistant by the EUCAST method and as resistant by ET DIR . Previous studies reported C. albicans and Candida kefyr isolates with the FKS1 mutations R647G and P649H and the above-mentioned phenotype using CLSI methods (19,20), thus suggesting that the amino acids R647 and P649 are key for glucan synthase inhibition by micafungin. Another study reported a C. tropicalis isolate harboring the F641L FKS1 mutation with dose-dependent susceptibilities to both micafungin and anidulafungin, again, by using CLSI methods (21).…”
Section: Discussionmentioning
confidence: 93%
“…However, a few major errors were found for anidulafungin in two C. tropicalis isolates with FKS1 mutations that were classified as anidulafungin-susceptible and micafunginresistant by the EUCAST method and as resistant by ET DIR . Previous studies reported C. albicans and Candida kefyr isolates with the FKS1 mutations R647G and P649H and the above-mentioned phenotype using CLSI methods (19,20), thus suggesting that the amino acids R647 and P649 are key for glucan synthase inhibition by micafungin. Another study reported a C. tropicalis isolate harboring the F641L FKS1 mutation with dose-dependent susceptibilities to both micafungin and anidulafungin, again, by using CLSI methods (21).…”
Section: Discussionmentioning
confidence: 93%
“…However, there is evidence that caspofungin MIC interlaboratory variability may lead to incorrect categorization of susceptibility results ( 36 ), and micafungin and anidulafungin MICs correlate better with the presence of FKS mutations and clinical outcomes ( 37 ). Resistance to echinocandins emerges as a result of treatment and has been associated with mutations in FKS 1/2 genes, which encode the target enzyme for this specific class of antifungals, β- D -glucan synthase ( 24 , 38 , 39 ). In agreement with what we know about more common Candida spp., investigators have recently identified novel and established FKS1 gene mutations in C. kefyr clinical isolates that are associated with in vitro echinocandin resistance ( 35 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The echinocandins were introduced in Europe and the United States beginning in 2001 and were incorporated into candidemia management guidelines as the first-line treatment in 2009 to 2012 (23)(24)(25)(26)(27). Following the increase in the use of the echinocandins, reports of acquired resistance among several different species, and especially C. glabrata, have been published (28)(29)(30)(31), thereby warranting continued surveillance and monitoring. The aim of this population-based nationwide study was to update and assess patterns of the incidence and susceptibility of fungemia in Denmark during a 12-year period.…”
mentioning
confidence: 99%